Do non-formal and informal adult education affect citizens’ political participation during adulthood? - Busse, Robin; Lischewski, Julia; Seeber, Susan (JSSE - Journal of Social Science Education, 2019)
Purpose: While research on political participation hardly takes into account the effects of non-formal or informal education, the effects of formal education are well investigated. The aim of this paper is to determine the extent to which non-formal and informal education contribute to adults’ participation in different political activities when formal educational background and other socioeconomic factors are controlled. Method: This paper uses data from the German National Educational Panel Study (NEPS, N=9,084). Binomial logistic regressions are used for the analyses, and average marginal effects (AMEs) are used for the model’s output. Findings: The findings reveal that non-formal and informal adult education significantly affect different political activities. However, the effects of non-formal and informal adult education differ with regard to the different forms of political participation. The results underline the importance of differentiated analyses of political participation and non-formal and informal adult education. In addition, the results show that some types of non-formal and informal education have a greater impact on adults of low socioeconomic status. Research limitations: This paper cannot account for self-selection effects because adults’ participation in different political activities was collected only in one wave.